Mode Effect and Response Rate Issues in Mixed-Mode Survey Research: Implications for Recreational Fisheries Management. (3rd July 2016) - Wallen, Kenneth E.; Landon, Adam C.; Kyle, Gerard T.; Schuett, Michael A.; Leitz, Jeremy; Kurzawski, Ken
Abstract: While the social, economic, and ecological impact of recreational fisheries is well established, the inherent diversity of both fisheries resources and resource users, particularly anglers, continues to present a challenge for management agencies. To better understand the diversity of recreational anglers, agencies often utilize survey methods to collect data on angler characteristics and preferences. However, obtaining necessary and representative data is becoming more challenging, exacerbated by declining response rates and an increase in the number of single and mixed-mode survey designs researchers can choose to collect data. We examined three survey designs—surface mail with a Web push, e-mail, and mixed mode—each with varying modes of solicitation and response, in the context of a statewide survey of licensed Texas anglers. Our findings illustrated that response rates varied considerably among these three survey designs. We also observed significant variation in terms of anglers' sociodemographic characteristics based on solicitation and response modes of each survey design. Interestingly, we observed limited variation in terms of anglers' behaviors, preferences, and motivations. Our results highlight the need for researchers and managers to be aware of the various survey designs available and the variability that particular survey designs can introduce into data. Received August 1, 2014; accepted March 2, 2016 Published online July 13, 2016